Optimization and Validation of a Real Time Reverse Transcriptase Polymerase Chain Reaction with RNA Internal Control to Detect Rubella RNA - Winny Xie; Yusmiati Yusmiati (The Indonesian Biomedical Journal, 2013)
BACKGROUND: According to a report from WHO, cases of rubella infection in Indonesia has increased up to 10-fold from 2007 to 2011. Despite no data of congenital rubella syndrome in the report, there are approximately 45,000 cases of babies born with heart failure and 0.1-0.3% live births with congenital deafness in Indonesia. Allegedly, rubella infection during pregnancy may play a role in this condition. This study aimed to optimize and validate a real-time reverse transcriptase polymerase chain reaction (RT-qPCR) method to detect rubella virus RNA as an aid for the diagnosis of congenital rubella infection.METHODS: Method optimization was conducted using nucleic acids extracted from Trimovax Merieux vaccine with the High Pure Viral Nucleic Acid Kit. One step RT-qPCR was performed with Quantifast Multiplex RTPCR+R Kit. Target synthetic DNA was designed and used to determine the sensitivity of the method. RNA internal control was synthesized to control the process of extraction and amplification.RESULTS: The analytical sensitivity of this method was as low as 5 copies target synthetic DNA/μl. The mean Coefficient of Variation (CV) % of the critical threshold (Ct) obtained were 2.71%, 1.20%, 1.62%, and 1.59% for within run, between run, between kit lots, and between operators, respectively. Recovery of the target synthetic DNA from amniotic fluid was 100.51% (by the log copies/μl) at the concentration of 1,000,000 copies/μl.CONCLUSION: RT-qPCR is successfully used for the detection of rubella virus RNA in vaccine and synthetic nucleic acid. With its high sensitivity, good precision and recovery, this method offers a means to improve the diagnosis of congenital rubella infection in developing countries like Indonesia.KEYWORDS: congenital rubella, RT-qPCR, prenatal diagnosis, amniotic fluid